Implementasi Pembelajaran Berbasis Kompetensi Dan Dampaknya Terhadap Hasil Belajar Bahasa Inggris Siswa SMP N Weliman: Studi Quasi-Experimental Dengan Pendekatan Mixed Method - bria, Bonefantura Jemy Bria; Yovince Abatan (SOKO GURU: Jurnal Ilmu Pendidikan, 2025)
Abstract. Background: Competency-Based Learning (CBL) has become an important paradigm in modern education, but its implementation in the context of English language learning in junior high schools still requires in-depth empirical studies. Objective: This study aims to analyze the implementation of competency-based learning and its impact on English language learning outcomes of students at Weliman State Junior High School through a quasi-experimental design with a mixed method approach. Method: The study used a nonequivalent control group design with 60 eighth-grade students as samples (30 in the experimental group, 30 in the control group). Quantitative data were collected through pretest-posttest English language learning outcomes, while qualitative data were obtained through learning observations, in-depth interviews with teachers and students, and analysis of learning documents. Results: Analysis of covariance (ANCOVA) showed a significant difference (F=45.23, p<0.001, η²=0.446) between the experimental and control groups after controlling for pretest scores. The experimental group showed an average score increase of 24.5 points (from 62.3 to 86.8), while the control group only increased by 8.7 points (from 61.8 to 70.5). Qualitative findings revealed that CBL implementation increased student motivation, encouraged more active and independent learning, and facilitated learning differentiation according to individual learning pace. Conclusion: Competency-based learning has been proven effective in improving junior high school students’ English learning outcomes and providing a more meaningful and personalized learning experience.